Asymmetric structure of bid-ask spreads across the business cycle. Issue 7 (2nd May 2016) - Lin, Chien-Chih
ABSTRACT: This study argues that the structure of bid-ask spreads is asymmetric across the business cycle. During expansion, investors tend to be overconfident, leading to a higher spread component due to information asymmetry. On the other hand, during recession, the markets are more volatile, leading to a higher spread component due to order processing costs. With TAIEX futures contracts as a sample, it is found that the spread component due to information asymmetry is significantly higher in times of expansion than in times of recession, while the spread component due to order processing cost is significantly higher in times of recession than in times of expansion.